THE IMPORTANCE OF VILLAGE GOVERNMENT LAW RENEWAL AND ITS IMPLICATIONS TO NAGARI GOVERNANCE IN WEST SUMATERA - Darmini Roza (Jurnal Dinamika Hukum, 2016)
The establishment of Rural Law is mandated by 1945 Constitution which provides recognition, status, law assurance, diversity, democracy and promote rural indigenous cultural traditions. The imple-mentation of Rural Law has implications towards nagari (village) governance which has to adjust it-self to the system and mechanisms stipulated in the Rural Law. Currently, government and West Su-matera Province regional house of representatives (DPRD) has established Regional Regulation draft on Principles of Nagari administration and waiting for Approval by the Ministry of Internal Affairs. The recognition of nagari as a traditional village and law community unit and the Indigenous communities require legal assurance and rights of origin enforcement as well as its authority in the effort of gov-ernance implementation and community empowerment. Nagari management prospects is West Suma-tera Regional Government agenda to empower villages through village budget aid despite its contro-versy  in terms of maintaining traditional culture of Salingka nagari.Keywords : village, village administration, legal instruments